The effect of predeparture training loads on posttour physical capacities in high-performance junior tennis players - Murphy, A. P.; Duffield, R.; Kellett, A.; Gescheit, D.; Reid, M. (International Journal of Sports Physiology and Performance, 2015)
Purpose: Difficulties in preserving physical capacities while on tennis tours necessitate targeted training prescription. This study analyzed training and match loads performed before and on tour for their relationship with posttour physical-capacity changes. A secondary aim was to determine whether the presence of a strength and conditioning (S&C) coach affected the type and volume of on-tour training load. Methods: The training and match loads of 30 high-performance junior tennis players were recorded over 8 wk: 4 wk before and 4 wk during an international tour. Fitness tests were conducted pretour and posttour, including double and single-leg (dominant and nondominant) countermovement jump, speed (5, 10, and 20 m), modified 5-0-5 agility, 10 × 20-m repeated-sprint ability, and multistage fitness tests. Tour training and match loads were categorized according to whether S&C support was present or absent. Results: Total and tennis training loads were significantly greater on tour than pretour (P = .05, d > 0.8). Increases in on-tour, on-court training loads were moderately correlated with decrements in speed and aerobic power (r = .31-.52). Finally, S&C presence on tour significantly increased total, on-court, and off-court training load completed (P = .05, d > 0.8). Conclusions: Training loads should be carefully prescribed to ensure that sufficient total and tennis loads are completed pretour. Specifically, speed and aerobic capacities may regress with increased training on tour. Finally, a practical observation was that on-tour S&C support resulted in increased S&C training load (around match loads), potentially countering the observed regression of physical capacities. Such a finding has the capacity to alter current physical-preparation structures in high-performance tennis environments with finite resources.